2019
DOI: 10.1111/joor.12838
|View full text |Cite
|
Sign up to set email alerts
|

Oro‐dental characteristics in patients with hypermobile Ehlers‐Danlos Syndrome compared to a healthy control group

Abstract: The Ehlers-Danlos syndrome (EDS) is a clinically and genetically heterogeneous group of heritable connective tissue disorders characterised by joint hypermobility, skin hyperextensibility and tissue fragility. 1 The estimated prevalence of Ehlers-Danlos syndrome is 1/5000, and the hypermobile EDS subtype (hEDS) is the most frequent. 2 EDS is caused by mutations in genes involved in collagen structure and/or biosynthesis, but the underlying pathophysiological mechanism is still not fully understood. 1 The clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Previous studies reported an increased prevalence of xerostomia and/or dry mouth sensation in patients with hypermobile-type EDS joint hypermobility. This observation may reflect the frequent multifactorial dysfunction frequently associated with EDS and indirectly increase the risk of caries [9,19].…”
Section: Salivary Functionmentioning
confidence: 96%
See 4 more Smart Citations
“…Previous studies reported an increased prevalence of xerostomia and/or dry mouth sensation in patients with hypermobile-type EDS joint hypermobility. This observation may reflect the frequent multifactorial dysfunction frequently associated with EDS and indirectly increase the risk of caries [9,19].…”
Section: Salivary Functionmentioning
confidence: 96%
“…Regarding the periodontal parameters, the authors found the plaque index to be significantly higher compared with the control group (mean, 0.396 vs. 0.059, p < 0.001). They also determined a greater attachment loss in the upper left and lower right upper molars and concluded that hypermobile-type EDS is associated with a potential predisposition to periodontal disease [9].…”
Section: Oral Characteristics Described In the Framework Of Ehlers-damentioning
confidence: 98%
See 3 more Smart Citations